Pengaruh Teknologi Informasi Dan Sistem Informasi Manajemen Terhadap Kualitas Layanan PT. Selalu Cinta Indonesia - Wulandari, Andriyani Putri; Syahrinullah, Syahrinullah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
The influence of technology and quality management information systems at PT.Selalu Cinta Indonesia is the purpose of this study. Technology and management information systems are programs that aim to improve the quality of the company. To meet the general information needs of all parties, the management information system provides information for all company employees in the form of periodic reports, special reports for information system purposes. The technique for the data collection process was carried out by giving a questionnaire with a sample size of 30 people. This type of research uses a qualitative descriptive method with a survey approach. The results of the study show that technology and systems have an effect on the quality of PT. Always Cinta Indonesia. With the research results 86.2% stated that the systems and technology owned by PT. SCI greatly influenced the quality of the company